The burden of bacteremia and invasive diseases in children aged less than five years with fever in Italy. Issue 1 (December 2015) - Azzari, Chiara; Moriondo, Maria; Di Pietro, Pasquale; Di Bari, Cesare; Resti, Massimo; Mannelli, Francesco; Esposito, Susanna; Castelli-Gattinara, Guido; Campa, Antonio; de Benedictis, Fernando; Bona, Gianni; Comarella, Lisa; et al.
Abstract Background Invasive diseases (ID) caused byStreptococcus pneumoniae (S. pneumoniae ), Haemophilus influenzae (H. influenzae ), andNeisseria meningitidis are a major public health problem worldwide. Comprehensive data on the burden of bacteremia and ID in Italy, including data based on molecular techniques, are needed. Methods We conducted a prospective, multi-centre, hospital-based study (GSK study identifier: 111334) to assess the burden of bacteremia and ID among children less than five years old with a fever of 39 °C or greater. Study participation involved a single medical examination, collection of blood for polymerase chain reaction (PCR) and blood culture, and collection of an oropharyngeal swab for colonization analysis by PCR. Results Between May 2008 and June 2009, 4536 patients were screened, 944 were selected and 920 were enrolled in the study. There were 225 clinical diagnoses of ID, 9.8 % (22) of which were bacteremic. A diagnosis of sepsis was made for 38 cases, 5.3 % (2) of which were bacteremic. Among the 629 non-ID diagnoses, 1.6 % (10) were bacteremic. Among the 34 bacteremic cases, the most common diagnoses were community-acquired pneumonia (15/34), pleural effusion (4/34) and meningitis (4/34).S. pneumoniae was the most frequently detected bacteria among bacteremic cases (29/34) followed byH. influenzae ( 3/34). Ninety percent (27/30) of bacteremic patients with oropharyngeal swab results were colonized with the studied bacterial pathogens compared to 46.1 % (402/872) of non-bacteremic cases (p < 0.001). PCV7 (7-valent pneumococcal conjugate vaccine) vaccination was reported for 55.9 % (19/34) of bacteremic cases.S. pneumoniae serotypes were non-vaccine serotypes in children who had been vaccinated. Mean duration of hospitalization was longer for bacteremic cases versus non-bacteremic cases (13.6 versus 5.8 days). Conclusions These results confirm thatS. pneumoniae is one of the pathogens frequently responsible for invasive disease.